Diskaprod: Dissemination and Creation of Basic Process Skills Assessment Instruments in Science Learning - Darmaji Darmaji; Astalini Astalini; Dwi Agus Kurniawan; Yusnidar Yusnidar; Harizon Harizon; Sarah Pramitha; Raden Muhammad Afrialdi (Integrated Science Education Journal, 2024)
Purpose of the Study: This research aimed to identify and analyze the outcomes of the DISKAPROD program, specifically focusing on assessing the effectiveness and quality of instruments used to measure students' basic process skills in schools. The study also sought to determine teacher perceptions regarding the program's impact on improving student learning outcomes. Methodology: A descriptive quantitative method was applied. The study population consisted of all teachers at the Al-Hidayah Foundation Kebon IX Muaro Jambi, with 21 teachers selected via purposive sampling. Data collection was conducted using questionnaires and interviews, while data analysis involved descriptive statistical tests to evaluate the teachers’ perceptions and responses to the program. Main Findings: The findings revealed strong teacher support for the DISKAPROD program. A significant 57.1% of the teachers expressed agreement with its implementation, and 76.1% provided a positive response to the program’s impact. These results suggest widespread approval and recognition of the program’s effectiveness in enhancing the measurement of student process skills, indicating the potential for broader adoption. Novelty/Originality of this Study: This study introduces a fresh approach by highlighting the critical role of teacher-developed assessment tools in accurately measuring student learning outcomes. The integration of the DISKAPROD program into the curriculum is presented as a novel and effective method for improving science education, particularly at the Mts level. By emphasizing the practical application of assessment instruments, this research contributes to ongoing efforts to refine educational practices and foster student skill development in scientific inquiry.